FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN PADA PASIEN PRE OPERASI BEDAH UMUM DI RUMAH SAKIT UMUM DAERAH KABUPATEN KEPULAUAN MERANTI - Nur Maimun; Debby Arini (Sistem Informasi, 2016)
Anxiety is a subjective experience of the individual and can not be observed directly as well as an emotional state without a specific object. Surgery or surgery is an action treatment using invasive way to open or display the body part being handled. Quantitative research methods with cross sectional study design with the general population of all surgical patients who will undergo surgery in hospitals district Meranti Islands in 2015 which amounted to 607 people. The result showed that there was significant relationship between traumatic events be at the level of anxiety Pvalue = 0.013 between the emotional conflicts with the level of anxiety Pvalue = 0.000 between Impaired self-concept and anxiety level Pvalue = 0.004 between physical disorder with anxiety level Pvalue = 0.001and the threat of self-esteem with the level of anxiety Pvalue = 0.000. It is recommended that the hospital more active role in providing information as well as procedures and actions to be taken so that patients who have a history of the disorder can prepare before surgery whether physical or psychological , which can provide beneficial effects for the patient .